2020
DOI: 10.3390/ijerph17103670
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Behaviors among 15–16-Year-Old Romanian High School Students: Results from Two Consecutive Surveys Related to Alcohol and Other Drug Use at the European Level

Abstract: The aim of this paper is to examine aggressive behaviors among Romanian high school students between 15 and 16 years old, to compare data in two national representative samples and to identify factors associated with physical fighting. This study investigates the association of selected factors (social, school performance and substance use) with physical fighting. A total of 2289 Romanian students were included in the 2007 database and 2770 in the 2011 database. This study revealed that 35.87% of the teenagers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
2
13
1
Order By: Relevance
“…The occurrence of self inflicted harm among adolescents is a self-destructive phenomenon and has a huge socio-psycho and health impact on individuals, families, friends and even communities [ 23 , 39 , 41 ]. This can be a huge problem for children and adolescents with both normal development and those with psychosocial disturbances [ 23 , 24 , 34 ]. Children and adolescents with such behaviour can also be destructive in nature and that includes a wide range of behaviors: explosive temper tantrums, physical aggression, fighting, threats or attempts to hurt others (including thoughts of wanting to kill others), use of weapons, cruelty toward animals, fire setting, intentional destruction of property and vandalism [ 27 , 34 , 39 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of self inflicted harm among adolescents is a self-destructive phenomenon and has a huge socio-psycho and health impact on individuals, families, friends and even communities [ 23 , 39 , 41 ]. This can be a huge problem for children and adolescents with both normal development and those with psychosocial disturbances [ 23 , 24 , 34 ]. Children and adolescents with such behaviour can also be destructive in nature and that includes a wide range of behaviors: explosive temper tantrums, physical aggression, fighting, threats or attempts to hurt others (including thoughts of wanting to kill others), use of weapons, cruelty toward animals, fire setting, intentional destruction of property and vandalism [ 27 , 34 , 39 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the children and adolescent population, there are various causes that make them susceptible to self inflicted harm such as poor relationship skills, substance abuse, underlying health causes and stress or frustration [ 22 , 34 , 36 ]. Sometimes adolescent population also face the problem of loneliness, has difficulty with social interaction and interpersonal communication that leads to impulsiveness and aggressiveness [ 24 , 27 , 29 ]. Numerous research studies and clinical trials have concluded on different aspects of child and adolescent population such as health behavior, mental and psychological issues and anxiety, depression, self-inflicted harm [ 2 , 3 , 14 ], and suicidal tendency and found a complex interaction of factors that led to an increased risk of violent and aggressive and self-inflicted harm behavior in children and adolescents [ 24 , 25 , 28 , 33 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, they display manifestations of anxious and depressive behavior ( Evren et al, 2015 ; Finning et al, 2019 ; Knollmann et al, 2019 ; Lawrence et al, 2019 ; Fornander and Kearney, 2020 ). These behaviors, characterized by a low emotional control, may lead to the manifestation of aggressive behavior as a means of escape ( Henry et al, 2012 ; Bucur et al, 2020 ; Fernández-Sogorb et al, 2020 ). According to Law et al (2011) , how an individual behaves in the face of distinct situations may have repercussions on the manifestation of emotions such as anger or aggression, thus increasing the risk of impulsive or aggressive behavior that may lead to school refusal ( Shaikh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A significant relationship was revealed to exist between both variables. Future studies should consider the need to design and offer educational strategies with specific intervention and prevention measures for use by schools and education specialists ( Bucur et al, 2020 ). Preventive interventions could be focused on improving the affective levels of all students, especially the most emotionally vulnerable, which would be positively reflected in the development and happiness of the students due to the relationship found between the school refusal behavior, affectivity, and aggression ( Sanmartín et al, 2018 ; Vicent et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents and young adults, the consequences of BD tend to be more common than adults, and BD can be associated with special negative health effects, such as hangover (headache and upset stomach) ( 8 ), increased risk of unplanned, unprotected sex ( 9 ) with consequent unplanned pregnancies, and/or sexually transmitted diseases (STD). BD was also related to higher rates of alcohol-related injuries ( 10 ) and violence ( 11 ), some of which were more common in boys, for example “physical fights” and “trouble with the police”, but both boys and girls who drank alcohol on more than three to five days in the last 30 days were involved in other problems, e.g. below average academic achievement ( 12 ).…”
Section: Introductionmentioning
confidence: 99%